Integrated Manufacturing-Services Businesses in the Australian Building and Construction Sector - Karen Manley (Australasian Journal of Construction Economics and Building, 2012)
This paper establishes that the emergence of integrated manufacturing-service businessesis a key trademark of innovative industries and ‘the new economy’. Having establishedthe benefits of such integration, the phenomenon is reviewed in relation to theAustralian building and construction (B&C) sector. It is hypothesised that manufacturerssupplying building and construction work are adding value to their own activity, and that ofthe sector, by enhancing their product offerings via the provision of services. A small surveyis undertaken, with the findings revealing the nature of service provision by manufacturersin the Australian B&C sector. It appears that the ‘bundling’ of products and servicesby these manufacturers is a key competitive strategy yielding significant benefits for themand the sector as a whole.